Caecal lymphangioma: a rare cause of gastrointestinal blood loss. (20th April 2013) - Rai, P; Rao, R N; Chakraborthy, S B D
Abstract : Lymphangioma is the malformation of the lymphatic system. Lymphangioma is a benign tumour and most colonic lymphangiomas do not cause symptoms and do not require treatment. Resection is required in patients with bleeding or intussusceptions. We report a case of intestinal lymphangiomatosis in a 31-year-old man who presented with recurrent melena and anaemia, which were diagnosed endoscopically and treated with surgical resection.